Human Resource Information System Social-Technical Aspects and Organizational Performance: The Role of Management Support in Tanzanian Universities - Innocent, Willy; Matoka, Chacha; Ngirwa, Charles (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2025)
This study examined the impact of Human Resource Information Systems (HRIS) on organizational performance at the University of Dar es Salaam (UDSM) and Mbeya University of Science and Technology (MUST) in TanzaniaThe research adopted a quantitative approach, collecting data from 260 supervisors across various departments. Using surveys and statistical analyses, the study investigated how HRIS’s social and technical aspects, coupled with management support, influenced institutional performance. The findings underscored the critical role of HRIS in enhancing efficiency, with management support significantly strengthening its effectiveness. Leadership engagement, continuous training, resource allocation, and improved communication emerged as essential factors in optimizing HRIS utilization. Additionally, findings showed that ensuring system accessibility and establishing regular evaluation mechanisms could enhance HRIS alignment with institutional goals. By addressing these areas, public universities in Tanzania can maximize the benefits of HRIS, ultimately improving operational efficiency and overall organizational performance.